AIRLINE CABIN AIR QUALITY - MAKI,D (Tufts Archival Research Center, 2007)
Testimony from the Association of Flight Attendants before the House Subcommittee on Aviation for a hearing on Airline Cabin Air Quality. Cites concerns flight attendants about cabin air quality on smoking and non-smoking flights. States that ventilation and filtration may not be sufficient to protect employees who spend many consecutive hours aboard airplanes.